In silico Screening of Potential Antidiabetic Phenolic Compounds from Banana (Musa spp.) Peel Against PTP1B Protein - Pratama, Rico Alexander; Astina, Junaida; Parikesit, Arli Aditya (Journal of Tropical Biodiversity and Biotechnology, 2023)
Type 2 diabetes mellitus (T2DM) is a global problem with increasing prevalence. The current treatments have made an immense progress  with some side effects, such as drug resistance, acute kidney toxicity, and increased risk of heart attack. Banana (Musa spp.) peel comprises 40% of banana fruit contains high phenolic compounds whilst some studies have suggested a correlation between phenolic compounds and antidiabetic activity. One of the novel protein targets that has been identified as a potential anti-diabetic treatment is PTP1B (PDB ID:2NT7). Therefore, this study aimed to screen the potential PTP1B inhibitor for antidiabetic treatment from phenolic compounds in banana peel. QSAR, molecular docking, ADME-Tox, and molecular dynamics analysis were deployed to examine forty-three phenolic compounds in banana peel. Eighteen ligands were screened by QSAR analysis and eight of them had a lower binding energy than the standard (ertiprotafib) in molecular docking, with urolithin A and chrysin were the lowest. Both passed Lipinski’s rule of five, had a good intestinal absorption, and no blood-brain barrier penetration, however, their mutagenicity, carcinogenicity, and irritation to the skin and eyes were still in questions. Molecular dynamics analysis found both of them were in a stable conformation with PTP1B. This study suggested a potential of urolithin A and chrysin as PTP1B inhibitor for antidiabetic treatment. Additionally, further experimentation is required to validate this finding.